Funeral Insurance: An Inter-Generational Commitment Device?. (22nd November 2017) - Berg, Erlend
Abstract: Funeral insurance is a global phenomenon that has existed throughout history and remains hugely popular in Africa today. Yet as a distinct financial device it has received little attention. The question is why it seems, in many contexts, to be preferred over standard life insurance even though the latter is a more flexible product. This paper presents a simple model in which funeral insurance differs from life insurance in that there is a constraint on how the payout is spent. Funeral insurance can therefore serve as an intergenerational commitment device. The model's key prediction is consistent with South African household data.